The Power of Irony: A Literary Analysis of Pegasus Olympus at War - Marpaung, Marlin Steffi (12th International Scholars Conference 2025, 2026)
This study examines Irony as a literary device in Pegasus Olympus at War by Kate O'Hearn, employing a qualitative descriptive method to analyze the function of Irony in the novel. The study aims to identify how Irony contributes to themes and character development in the young adult fantasy genre, which is entitled Pegasus Olympus at War. Through a detailed analysis of dialogue and narrative context in the novel, 24 of Irony were identified and categorized into nine situational ironies, thirteen verbal ironies, one combining verbal and situational Irony, and one combining verbal, situational, and dramatic Irony. The results reveal that verbal Irony was the most commonly found in Pegasus Olympus at War, mostly through the characters in the novel. Verbal Irony creates humour, expresses scepticism, and critiques the absurdities, while the situational Irony emerges through unexpected reversals, and often highlights the capability of mortal characters over their mythological counterparts. The combined forms of Irony add narrative complexity as well as emotional depth. The study concludes that Irony in the novel is a stylistic device and a powerful narrative strategy that enhances the story's realism, relatability, and thematic richness, making it more engaging and meaningful for young adult readers.